Use of Social Networking Sites at Workplace in Bangladesh: Employees’ Perspective - Siddique , Tabassum (i-Proclaim, 2015)
The growing use of online social networking in today’s business activities have become an integral part of a modern organization in Bangladesh. It has recently taken the place of real life social networks and communication in all aspects of life. The cheap availability of Internet through the computer, Laptop and some other handheld devices provided by most of the modern private organizations, are giving its employees a privilege of getting easy access to their personal and professional social networking sites at home and at work. Organizations spend money for such purposes as an investment on a strategic tool for enhancing the productivity of its employees. Social networking sites at the workplace carry enormous benefits and some drawbacks as well. This could hinder organizational productivity and reputation if not managed effectively. One of the prominent managerial tools is organizational policy regarding the use of social networking sites at work.  The present study attempts to investigate the usage, activities and impacts of using social networking sites by the employees at the workplace. The study also intends to guide the employers to introduce a reasonably fair guidance that will be acceptable by both the parties. The study used a sample of 180 employees working at different organizations in Dhaka city. Proper guidance, educating and training employees about the security issues for the organization, allowing employees time based access, etc. are some of the major recommendations made by this paper that can work for the company without limiting the employee freedom.